HUBUNGAN ANTARA PELAYANAN PENGELOLA TBM “SANGKA MAMBACO” DENGAN INTENSITAS KUNJUNGAN MASYARAKAT DI TAMAN BACA MASYARAKAT JORONG PASAR KECAMATAN LIMA KAUM KABUPATEN TANAH DATAR - Drajat, Zikri; Ismaniar, Ismaniar (Universitas Negeri Padang, 2023)
The research background is the low intensity of community visits to community reading gardens in Lima Kaum District. This is presumably because the services of the management of TBM